“Calma Clima”: The Story Behind the Largest Informal Running Group in the World (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2025)
Born in 2017, “Calma Clima”, an informal running group created by Bernardo Biagioni in Belo Horizonte, proposes to individuals the recognition and appropriation of the body and urban spaces, by pioneering and calling for the occupation of the city through the democratization of sport and leisure. With the aim of researching this phenomenon, which engages thousands of followers on its social network and takes hundreds of participants to the streets of the capital of Minas Gerais every week, we seek, through oral history and online sources, to trace some paths that tell the story of this project , in order to instigate new studies, actions, possibilities and reflections, regarding the promotion of leisure, sport and territory, through initiatives linked to the uses of virtual social networks, and the possible impacts on contemporary society.